Effects of hamstring stretching exercises on the toe-touch test in elementary schoolchildren - Sainz de Baranda, P.; Rodriguez, P. L.; Santonja, F. M.; Lopez, P. A.; Andujar, P.; Ferrer, V.; Pastor, A. (Journal of Human Movement Studies, 2006)
The purpose of the study was to investigate the effect of a stretching exercise program on hamstring flexibility in prepubertal schoolchildren. A total of 62 children were divided into two groups (experimental group and control group). The experimental group (n=45; 22 boys and 23 girls) performed hamstring Stretches for 5 minutes during the Physical Education classes over a füll school term (9 months), two sessions per week (31 weeks, 62 sessions of Physical Education). The control group (n=18; 9 boys and 9 girls) followed the Standard class program of Physical Education classes. Hamstring flexibility was measured using the toe-touch lest before and after the program. No significant differences were revealed in hamstring flexibility before and after the Physical Education classes for the control group. However, significant improvements were shown in the experimental group (p<0.001). It is concluded that a füll school term (9 months) incorporating static stretching äs part of the Physical Education classes and the school physical activities significantly increases the flexibility of the hamstrings in prepubertal schoolchildren.